Flexural Performance of Concrete Beams Reinforced with Basalt Fiber Reinforced Polymers (BFRP) Bars - Al-Mimar, Mustafa Adel Muhsin (2019)
A Master of Science thesis in Civil Engineering by Mustafa Adel Muhsin Al-Mimar entitled, “Flexural Performance of Concrete Beams Reinforced with Basalt Fiber Reinforced Polymers (BFRP) Bars”, submitted in May 2019. Thesis advisor is Dr. Farid Abed. Soft and hard copy available.